Correlation analysis of optimal orientation and tilting of PV array using various types of solar database - Koh, Yong Ser (2024)
This project investigates the optimal tilt angle and orientation for photovoltaic (PV) systems in tropical regions. Recognizing the limitations of previous research, this study expands the scope by considering a broader range of locations, orientations, and interrow spacing (DL ratio) while incorporating the Perez sky model to accurately account for diffuse radiation components. The research utilizes simulated data from both SolarGIS and PVGIS databases, employing Typical Meteorological Year (TMY) and Time Series (TS) data types to determine optimal parameters that maximize global tilted irradiance (GTI). The analysis reveals that the results from both TMY and TS data are close enough to suggest their universality, allowing for the use of TMY data to significantly reduce simulation time without sacrificing accuracy, as TMY provides representative weather data. Optimal tilt angles generally increase with latitude, aligning with theoretical expectations but deviating at lower latitudes, likely due to the influence of tropical climate factors. Optimal orientation shows a distinct shift from south to southeast and east as latitude decreases, challenging the conventional assumption that south-facing panels are universally ideal. Further analysis establishes a DL ratio of 1.5 as ideal for achieving consistent performance, balancing interrow shading with efficient land usage. Interestingly, the study demonstrates that minor variations in tilt angle (±3°) and orientation (±30°) have a negligible impact on energy production, providing flexibility during installation. Additionally, the simulation's accuracy is validated through comparison with experimental data collected from a PV system in Malaysia. The experimental results, while limited in scope due to practical constraints, align with the simulated predictions, particularly regarding optimal orientation. This research provides insights for PV system designers and installers in tropical regions, emphasizing the significance of latitude-specific adjustments and interrow spacing optimization. The findings contribute to a deeper understanding of the interplay between geographical factors and PV system configurations for maximizing energy yield in tropical climates.